An acquired stable variant of a dicentric dic(9;20) and complex karyotype in a Syrian childhood B-acute lymphoblastic leukemia case - Abdulsamad Wafa; Rami A. Jarjour; Abdulmunim Aljapawe; Suher ALmedania; Thomas Liehr; Joana B. Melo; Isabel M. Carreira; Moneeb A. K. Othman; Walid Al-Achkar (Molecular Cytogenetics, 2020)
Abstract Background About 25 years ago, the acquired chromosome abnormality dicentric dic(9;20)(p11 ~ 13;q11) was seen described as a non-random aberration in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). Yet, about 200 cases were reported. However, dicentric dic(9;20) is a subtle abnormality which easily may be mixed up with monosomy 20 and/or del(9p). The dicentric dic(9;20) can be found as a sole chromosomal abnormality or can be masked within complex rearrangements; also, a dicentric dic(9;20) is often associated with mono- or biallelic loss of CDKN2A gene. Case presentation Here we report a case of 16-year-old male diagnosed with a de novo pre-B-ALL. Molecular approaches (array-based multicolor banding (aMCB) and array comparative genomic hybridization (aCGH)) were applied, and a unique complex karyotype involving six chromosomes was identified. It included three previously unreported chromosomal aberrations: dicentric dic(9;20;X), deletion del(7)(p22.2p15.2) and dicentric dic(7;13). The dicentric dic(9;20;X) also led to monoallelic loss of tumor suppressor gene CDKN2A. After successful chemotherapeutic treatment the patient experienced a relapse with a secondary ALL without complex karyotype but a deletion del(19)(p13). Unfortunately, the patient died after 17 months of the initial diagnosis. Conclusions To the best of our knowledge, a comparable childhood ALL associated with such complex karyotype and deletion del(19)(p13) in secondary ALL was not previously reported. Thus, the complex karyotype with dicentrc dic(9;20;X) seems to indicate for a poor prognosis.